Phloroglucinol and Terpenoid Derivatives from Hypericum cistifolium and H. galioides (Hypericaceae) - Crockett, Sara L.; Kunert, Olaf; Pferschy-Wenzig, Eva-Maria; Jacob, Melissa; Schuehly, Wolfgang; Bauer, Rudolf (Frontiers in Plant Science, 2016)
A new simple phloroglucinol derivative characterized as 1-(6-hydroxy-2,4-dimethoxyphenyl)-2-methyl-1-propanone (1) was isolated from Hypericum cistifolium (Hypericaceae) as a major constituent of the non-polar plant extract. Minor amounts of this new compound, in addition to two known structurally-related phloroglucinol derivatives (2 and 3), and two new terpenoid derivatives characterized respectively as 2-benzoyl-3,3-dimethyl-4R,6S-bis-(3-methylbut-2-enyl)-cyclohexanone (4a) and 2-benzoyl-3,3-dimethyl-4S,6R-bis-(3-methylbut-2-enyl)-cyclohexanone (4b), were isolated from a related species, H. galioides Lam. The chemical structures were established using 2D-NMR spectroscopy and mass spectrometry. These compounds were evaluated in vitro for antimicrobial activity against a panel of pathogenic microorganisms and anti-inflammatory activity through inhibition of COX-1, COX-2 and 5-LOX catalyzed LTB4 formation.